Definition, diagnosis and management of fetal lower urinary tract obstruction: consensus of the ERKNet CAKUT-Obstructive Uropathy Work Group - Capone, Valentina; Persico, Nicola; Berrettini, Alfredo; Decramer, Stèphane; De Marco, Erika Adalgisa; De Palma, Diego; Familiari, Alessandra; Feitz, Wout; Herthelius, Maria; Kazlauskas, Vytis; Liebau, Max Christoph; Manzoni, Gianantonio; et al. (Nature reviews. Urology, 2022)
Fetal lower urinary tract obstruction (LUTO) is associated with high mortality and postnatal morbidity caused by lung hypoplasia and impaired kidney function. Specific diagnostic features that can guide clinical approach and decisions are lacking; thus, the European Reference Network for Rare Kidney Diseases established a work group to develop recommendations regarding the clinical definition, diagnosis and management of prenatally detected LUTO. The work group recommends the use of antero-posterior diameter of renal pelvis as the most reliable parameter for suspecting obstructive uropathies and for suspecting prenatal LUTO in the presence of fetal megacystis. Regarding prenatal and postnatal prognosis of fetuses with LUTO, the risk of fetal and neonatal death depends on the presence of oligohydramnios or anhydramnios before 20 weeks’ gestation, whereas the risk of kidney replacement therapy cannot be reliably foreseen before birth. Parents of fetuses with LUTO must be referred to a tertiary obstetric centre with multidisciplinary expertise in prenatal and postnatal management of obstructive uropathies, and vesico-amniotic shunt placement should be offered in selected instances, as it increases perinatal survival of fetuses with LUTO.
Gesehen am 15.08.2023